IMPLEMENTASI âAL-âUQUD AL-MURAKKABAHâ ATAU âHYBRID CONTRACTSâ (MULTI AKAD) GADAI EMAS PADA BANK SYARIAH MANDIRI DAN PEGADAIAN SYARIAH - Sahal, Lutfi (At-Taradhi, 2015)
The practice of gold pawning in Bank SyariahMandiri and Pawn often reapsthe doubting regarding the correctness of these products. These doubts arise because of the imposition of a multi contract. Likewise the use of multi-contract and calculation of the cost of storage leases (Ijara) carried out by the Islamic pawnshop raised doubts about the correctness of the sharia pawn contract. The doubt arises because there is a provision of Law Compilation of SyariahEconomics and DSNMUI Fatwa which has been violated. The aim of this study was to obtain an overview of the settings in practice use of multi syariah pawn contract in the contract carried out by the Islamic pawnshop connected with Perma No. 2 In 2008 about Law Compilation of Islamic Economics as well as to obtain certainty about the legal consequences of Storage Fee Calculation Lease (Ijara) in the lien contract carried out by the Islamic pawnshop associated with DSN MUI Fatwa No. 25 / DSN-MUI / III / 2002 on Rahn.